Numerical Modeling Strategy for the Simulation of Nonlinear Response of Slender Reinforced Concrete Structural Walls - Mohammed, Mohammed A.; Barbosa, Andre R. (Computer modeling in engineering & sciences, 2019)
A three-dimensional nonlinear modeling strategy for simulating the seismic response of slender reinforced concrete structural walls with different cross-sectional shapes is presented in this paper. A combination of nonlinear multi-layer shell elements and displacement-based beam-column elements are used to model the unconfined and confined parts of the walls, respectively. A uniaxial material model for reinforcing steel bars that includes buckling and low-cyclic fatigue effects is used to model the longitudinal steel bars within the structural walls. The material model parameters related to the buckling length are defined based on an analytical expression for reinforcing steel bars embedded in reinforced concrete elements, which are developed based on beam-on-springs model, and validated with experimental tests of boundary elements of structural walls available in the literature. Six experimental case studies of reinforced concrete walls with rectangularshape, T-shape, and U-shape cross-section are used to validate the structural wall numerical modeling strategy.